PKM KELOMPOK TANI JAYA DESA NITAKLOANG KECAMATAN NITA KABUPATEN SIKKA - Wahyuni, Yuyun; Ma, Stefanus Hubertus Gusti; Apelabi, Gabriel Otan; Bolly, Yovita Yasintha; Nunung, Agnes Yuniati; Alfredo, Jefrisko; Kelen, Ursula Uto; Nitit, Daminanus Tega (LPPM Universitas Flores, 2024)
The partner in this community service activity is the Jaya Farmer Group in Nitakloang Village, Nita District. This group was formed in 2021 according to the decree of the Head of Nitakloang Village. The Jaya Farmer Group has had 11 members since its formation. The results of a survey conducted by the PKM team found. The problems faced by partners in carrying out corn farming are the lack of knowledge and skills of farmers in carrying out post-harvest handling so that when production results are high, farmers experience difficulties in handling which results in damage to corn commodities. The solution to this problem in the Jaya Farmer Group is through mentoring and training on post-harvest handling of corn. Method: A more effective extension method is needed for farmers to accept and implement post-harvest technology. One extension method that is considered quite effective is the demonstration extension method. Demonstration method showing a new way of working or a method that has been improved. The technological transformation process will be easy with this dem car method because the farmer's senses are focused on what is being demonstrated.